ChemInform Abstract: Efficient Metal‐Free Aerobic Photooxidation of Sulfides to Sulfoxides Mediated by a Vitamin B2 Derivative and Visible Light. Issue 39 (September 2016) - Nevesel, Tomas; Svobodova, Eva; Chudoba, Josef; Sikorski, Marek; Cibulka, Radek
Abstract: The method is chemoselective, producing sulfoxide without overoxidation to sulfones.